Effects Of Genre Based Approach (GBA) In EFL Reading Comprehension And Writing (GIST – Education and Learning Research Journal, 2019)
The present paper puts under examination the effects of Genre Based Approach (GBA) on 9th grade students from a city in the Caribbean coast of Colombia. The study has the purpose of analyzing how GBA affects reading comprehension and writing. We implemented GBA for six sessions using instruments for data collection that included tests, questionnaires and interviews. The overall findings show that students’ reading comprehension, writing, motivation and autonomy improve after the implementation of GBA; as a result, the students were able to understand, explain and recreate the genres that were part of the study.
Keywords: GBA; genre awareness; reading comprehension; writing; autonomy